On financial development and economic growth in Egypt. Issue 2 (15th November 2019) - Mohieldin, Mahmoud; Hussein, Khaled; Rostom, Ahmed
Abstract : Purpose: This paper aims to discuss the evolution of the Egyptian banking sector and the main trends in financial development in Egypt. The purpose of this study is to examine empirically the relationship between the development of the financial sector and economic growth in Egypt between 1980 and 2016. Design/methodology/approach: The paper draws comparisons based on critical financial indicators between Egypt and selected emerging markets and developing economies. It uses a new data set of financial development indexes released by the International Monetary Fund. This paper uses econometric time series modelling of bivariate regressions for real growth per capita and measures of financial development to assess the relationship between financial development and economic growth in Egypt. Findings: There are three specific findings based on the empirical analysis. First, there is a strong association between real growth per capita and financial development measured by money supply to GDP. Second, access to and the efficiency of banking services are not associated with real per capita income. Third, the Financial Markets Access Index – which compiles data on market capitalization outside of the top ten largest companies and the number of corporate issuers of debt – indicates a robust association with real per capita GDP. Originality/value: The paper uses advanced empirical investigation techniques and new data sets available to assess the critical relationship between finance and growth in Egypt. The main policy implications of the empirical results of this paper suggest a stronger focus on promoting a more proactive role for the financial services industry in Egypt. In particular, there is a critical role for bank financing to support the private sector to maintain an inclusive growth momentum. Further development of the capital market will promote sustainability of such economic growth.